The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/smtd.202100109
|View full text |Cite
|
Sign up to set email alerts
|

Modulating the 0D/2D Interface of Hybrid Semiconductors for Enhanced Photoelectrochemical Performances

Abstract: Despite major progress, these materials still face several significant challenges. In particular: 1) metal oxides usually possess a large bandgap that limits the sunlight absorption, 2) not all metal oxides have a favorable band alignment to realize both redox processes (water reduction and oxidation), 3) low electrical conductivity and limited hole diffusion length, 4) charge recombination can occur easily in the bulk and on the surface, limiting the efficiency of the system.Recently, extensive efforts have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…It has been demonstrated that the performance of photodetectors is significantly improved by integrating QDs as light-absorbing layers or active layers. [21][22][23][24][25][26]72 In addition, high-performance photodetectors decorated by QDs are also attracting increasing attention thanks to their great lightharvesting abilities and charge transfer characteristics. [27][28][29]46 As an example, Bi et al demonstrated that the photocurrent of a ZnO NWs device was enhanced from 0.167 to 1.84 mA by decorating binary CdS QDs.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the performance of photodetectors is significantly improved by integrating QDs as light-absorbing layers or active layers. [21][22][23][24][25][26]72 In addition, high-performance photodetectors decorated by QDs are also attracting increasing attention thanks to their great lightharvesting abilities and charge transfer characteristics. [27][28][29]46 As an example, Bi et al demonstrated that the photocurrent of a ZnO NWs device was enhanced from 0.167 to 1.84 mA by decorating binary CdS QDs.…”
Section: Introductionmentioning
confidence: 99%
“…The consumption of holes can ensure that the subsequent holes continue to migrate and improve the PEC efficiency. Commonly used sacrificial agents in PEC systems include Na 2 S-Na 2 SO 3 [20,21] , triethanolamine (TEOA) [22,23] and H 2 O 2 [24][25][26] and these have been widely used to evaluate interfacial charge transfer properties. Thorne et al measured the photocurrent-voltage curves of a hematite photoanode and found that the photoanode with H 2 O 2 as hole scavengers has lower onset potential values [24] .…”
Section: Hole Sacrificial Agentsmentioning
confidence: 99%
“…Recently, 0D/2D heterojunctions have attracted much attention because of their excellent interfacial charge transfer characteristics [33–35] . Specifically, 0D nanoparticles have shorter charge transfer distances, and 2D nanosheets as carriers can avoid the self‐aggregation of 0D nanoparticles, which can provide more migration paths for the effective separation of photogenerated charge carriers [36,37] . Inspired by this, exploring an appropriate 0D semiconductor to compound with 2D LaTiO 2 N is expected to further improve the photocatalytic CO 2 reduction activity of LaTiO 2 N.…”
Section: Introductionmentioning
confidence: 99%